(3GdEJUGd GddGYfaj (B:s (3hbaI YfO fXQI(B" (3eGQTGd QhRfHQZ(B" /s - (3HhcQjSI, YGFTIs ((3GdbHI GdLRGFQ (B:s (3OGQ GdNdOhfjI ddfTQ h GdJhRjY ,s, 2013)
(3jYO cJGH eGQTGd QhRfHQZ (B"(3GdJhGUd GddGYfaj(B" (3CMO CcKQ GdcJH GdMOjKI JCKjQkG aj eLGd GdJhGUd(B. (3hgh jMOO WQjbI JhGUd LOjOI JSJNOe aj GdehGba GdTNUjI Ch GdegfjI(B. (3jecf ddeaGgje GdehVMI aj gPG GdcJGH Cf JZjQ MjGJc ddCaVd(B. (3HeLQO Cf JbQCg, df JfXQ Edi GdJhGUd HfaS GdWQjbI eQI CNQi(B.s
Keywords: (3GdGJUGd GddGYfajs; (3eGQTGd QhRfHQZs; communication non violente